Durability of Asphalt Mixture AC-WC Using Latex Based on the Test Method of SNI 6753:2015 - Sri Sunarjono; Bima Hardi Anto; Nurul Hidayati; Senja Rum Harnaeni (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This paper reports the results of an investigation of the durability of the AC-WC mixture using latex based on the SNI 6753:2015 test method. This method uses a test object with a low density (7% air void), while another method, namely Bina Marga (BM) 2018 which is more often applied in the field, uses a normal density test object (air void 4%). The product of these two different methods needs to be evaluated. On the other hand, the performance of latex on the durability of the AC-WC mixture at low density also needs to be studied. The main objective of the research is to study the durability of the AC-WC mixture using latex based on the SNI test method, compare it with the BM method, and at the same time evaluate these two test methods. The research method used is to conduct durability tests in the laboratory on test objects with low and normal densities. Two types of specimens were prepared, namely without and with latex, both were tested in conditions without and with immersion. The properties of the test object were evaluated using Indirect Tensile Strength (ITS). The test results were studied and compared, including to evaluate the two test methods. The results of the study concluded that the AC-WC mixture at low density (7% air void) had high durability with an IKS value above 90%. The value of the durability of the mixture is higher when using latex and at normal density (4% air void). The SNI 6753:2015 test method that uses 7% air void specimens is more recommended for evaluating the durability of asphalt mixtures.